Pengaruh Kualitas Produk Promosi dan Desain Terhadap Keputusan Pembelian Motor Yamaha Fazzio di Bekasi - Rachma, Faizah (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
The aim of this research is to analyze the influence of product quality, promotion and design on purchasing decisions in the Bekasi City community. The population of this research is PT Yamaha Mega Bekasi customers, namely 75 respondents. The sample used in this research was part of the customers who purchased or used Yamaha Fazzio motorbike products at PT Yamaha Mega Bekasi who resided in Bekasi. The technique used in this sampling was purposive sampling technique, the data analysis tool used was multiple linear regression analysis using the SPSS program. The results of testing the hypothesis show that the variable: product quality has a positive and insignificant effect on purchasing decisions. Promotion has a positive and insignificant effect on purchasing decisions. And design has a positive and significant effect on purchasing decisions. The coefficient of determination (Adjusted R2) obtained was 0.321. This means that 32.1% of purchasing decisions can be explained by the variables product quality, brand image and price perception, while the remaining 67.9% can be explained by variables other than these three variables.